Métis Research Ethics: Academic Freedom and Métis Government Accountability - Fiola, Chantal (Pawaatamihk, 2025)
The Métis author shares her experiences navigating relationships with the Manitoba Métis Federation (MMF) across her research studies on Métis spirituality, especially relationships with traditional Indigenous ceremonies, underscoring ethical considerations. Recent efforts by the MMF to assert sovereignty as a safeguard against Métis identity fraud and subsequent impacts on Métis research and scholarship are also discussed. The argument proposed is that the academic freedom of Métis citizen scholars need not be pitted against Métis government efforts at sovereignty—rather than viewing these as mutually exclusive, they can co-exist to promote ethical Métis scholarship and self-determination.